Mini review : Nitrite reductase and biosensors development - Siti Nur Syazni, Mohd Zuki; Nina Suhaity, Azmi; Ling, Tan ling (Hibiscus Publisher, 2014)
Nitrite ions have emerged as one of the major problems in environmental and pollution issues nowadays. Food products are the major source of these ions to preserve color. However, there is a maximum permissible limit (MPL) for the use of nitrite in food. A lot of works in the literature have been carried out on nitrite quantification and most of them are using simple and quick analysis methods. Recently, the advent of biosensor has allowed the fabrication of sensors for the detection of nitrite. This paper specifically reviews the interest in the usage of the nitrite reductase enzyme as a biorecognition element for the application of nitrite biosensors.